When Governments and International Organizations Shut Down: The Impact of COVID-19 on Refugees’ and Host Community’s Use of Educational Services in Cox’s Bazar - Gjerløw, Haakon; Karim, Sabrina; Østby, Gudrun (Frontiers in Education, 2021)
At the global level, COVID-19 not only shut down many services that national governments provide to public, but it also severely limited the ability of international organizations to deliver services during humanitarian crisis. We suggest that the absence of governments and INGOs creates a vacuum for informal institutions to increase their reach. In this research note, we present novel phone survey data on education services in Cox’s Bazar, Bangladesh with host communities and refugees. We show that the number of households without access to education decreased during lockdown, but that the impact was different for the refugee population and the host population. This is because the refugee community relied on their prior ties to informal education, whereas the host community did not have the same ties to multiple informal options. Overall, we show that informal institutions provide a substitute for governments and international organizations when they shut down.